2007
DOI: 10.1089/pho.2007.2113
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Protoporphyrin-IX in Rat Leydig Cells Following Induction by 5-Aminolevulinic Acid and Tramadol

Abstract: The results suggested that in R(2)C cells, exogenous ALA and tramadol induced protoporphyrin accumulation. This information is useful for two reasons. First, it may help to diminish pain after ALA-PDT treatment; and second, it allows the use of lower concentrations of ALA during therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…ALA is a known precursor of PPIX [20], [28], [29], which indeed induced accumulation of PPIX in ES cells (Fig. 5D).…”
Section: Resultsmentioning
confidence: 83%
“…ALA is a known precursor of PPIX [20], [28], [29], which indeed induced accumulation of PPIX in ES cells (Fig. 5D).…”
Section: Resultsmentioning
confidence: 83%
“…Tramadol is a safe and well‐tolerated centrally acting, narcotic‐like analgesic indicated for the management of moderate to moderately severe pain in adults and is available in both short‐ and long‐acting formulations. It has been suggested that in rat Leydig cells (R 2 C), exogenous ALA and tramadol induced protoporphyrin accumulation could possibly help to diminish pain after ALA‐PDT treatment and allow for the use of lower concentrations of ALA during therapy .…”
Section: Introductionmentioning
confidence: 99%